Characterization of endozoochorous dispersal of pitayo Stenocereus queretaroensis, in Autlán, Jalisco, Mexico. Issue 5 (3rd September 2018) - García-Ruiz, Miriam; Ruán-Tejeda, Irma; Zuloaga-Aguilar, Martha S.; Íñiguez-Dávalos, Luis I.
Abstract : HIGHLIGHTS We compared dispersion by two species of bats with two species of birds, and concluded that bats are more efficient dispersers of this columnar cactus. The importance of specific plant-animal interactions for the fitness of the interacting groups is mostly driven by the morphological, physiological and behavioural traits of the two interacting species. This work aims to describe dispersal of seeds of the columnar cactus Stenocereus queretaroensis by its main fruit consumers (bats and birds), using the criteria of legitimacy and efficiency. A disperser is legitimate when seeds pass through the gut without losing germination capability, and is efficient if the seeds are transported to places where they have the potential for germination and establishment as seedlings. We conducted direct observations in order to identify the main consumer species of S. queretaroensis fruits. Seed germination was evaluated by comparing those that pass through the gut of two bat species, Artibeus lituratus and Leptonycteris yerbabuenae, and two bird species, Icterus pustulatus and Melanerpes chrysogenys, using the parameters germination percentage and germination rate. To evaluate seed deposition patterns by bats and birds within the study area, 20 seed traps were set: 10 below the canopies of local trees, and 10 in open spaces. Nine species of bats and 13 species of birds were found to consume S. queretaroensis fruits. The four tested species can be considered legitimate dispersers, but germination percentage differed among these disperser species. Seeds defecated by birds show the highest speed of germination and lowest average time to germinate, compared with control seeds. In terms of deposition patterns, however, the bats dropped the highest number of seeds, and deposited them both under the canopy and in open areas, whereas birds drop a lower amount and under the canopy only.